2016
DOI: 10.1126/scisignal.aad4403
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, structure, and evolution of nitric oxide synthase–like proteins in the plant kingdom

Abstract: Nitric oxide (NO) signaling regulates various physiological processes in both animals and plants. In animals, NO synthesis is mainly catalyzed by NO synthase (NOS) enzymes. Although NOS-like activities that are sensitive to mammalian NOS inhibitors have been detected in plant extracts, few bona fide plant NOS enzymes have been identified. We searched the data set produced by the 1000 Plants (1KP) international consortium for the presence of transcripts encoding NOS-like proteins in over 1000 species of land pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(115 citation statements)
references
References 61 publications
0
99
2
Order By: Relevance
“…Given that NO is generated in S-deprived cells (Minaeva et al, 2017), the increase in THB1 transcription detected during S limitation may reflect NOS activity. Recently, several algae were shown to contain NOS (Foresi et al, 2010;Jeandroz et al, 2016). This, however, did not appear to be the case in our experiments.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Given that NO is generated in S-deprived cells (Minaeva et al, 2017), the increase in THB1 transcription detected during S limitation may reflect NOS activity. Recently, several algae were shown to contain NOS (Foresi et al, 2010;Jeandroz et al, 2016). This, however, did not appear to be the case in our experiments.…”
Section: Discussioncontrasting
confidence: 55%
“…In Chlamydomonas, it has been reported that THB1 is induced by nitrate (Johnson et al, 2014). Moreover, THB1 is highly expressed in the presence of NO (Sanz-Luque et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Taxons where this protein was identified are indicated in parenthesis after the name of each group. The image has been taken and adapted from Jeandroz et al (2016) and Rensing (2016).…”
Section: Uvr8 Mechanism Of Action and Evolutionary Conservationmentioning
confidence: 99%
“…27 Our previous research have found that hydrogen peroxide, NO, Ca 2C ions and calmodulin were involved in adventitious root development. 38 suggesting that NR-associated NO production is main pathway involved in H 2 -induced rooting. Three rootingrelated enzymes, peroxidase, polyphenol oxidas and indoleacetic acid oxidase were involved in H 2 -indcued adventitious rooting through NO pathways.…”
Section: 24mentioning
confidence: 99%